Evidence of Diamond Nanowires Formed inside Carbon Nanotubes from Diamantane Dicarboxylic Acid1. Issue 13 (18th February 2013) - Zhang, Jinying; Zhu, Zhen; Feng, Yanquan; Ishiwata, Hitoshi; Miyata, Yasumitsu; Kitaura, Ryo; Dahl, Jeremy E. P.; Carlson, Robert M. K.; Fokina, Natalie A.; Schreiner, Peter R.; Tománek, David; Shinohara, Hisanori
<x xml:space="preserve">Abstract</x> Carbon is a girl′s best friend: Carbon‐based nanowires have been produced during thermal annealing of diamantane‐4, 9‐dicarboxylic acid in carbon nanotubes under hydrogen atmosphere (see scheme). HR‐TEM images, Raman spectra, and structural transformations observed under an intense electron beam suggest that the as‐produced carbon‐based nanowires are sp3 diamond nanowires, consistent with our computational results.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>